Reading difficulties & dyslexia : essential concepts and programs for improvement - Das, J. P. (Jagannath Prasad) (SAGE Publications, Inc., 2020)
Previously, dyslexia was defined as primarily a deficit at the word reading level. When the original edition of this book was published, the core deficit was thought to be phonological coding. The search for a single factor for dyslexia is no longer pursued. However, we must explore why approximately 15 per cent of school children have difficulties in learning to read or doing math. This updated edition offers an explanation based on contemporary developments in the study of cognition and neuroscience. It also studies the impact of poverty on learning, a relatively new but extremely important area of interest. Going beyond a simple view of reading and math, Reading Difficulties and Dyslexia discusses distal factors such as cognitive flexibility and attentional control. A distinguishing feature of this book is that it presents intervention programmes, based on the distal factors, which can greatly improve word decoding and comprehension, and enhance number sense.